Addressing data gaps in marine litter distribution: Citizen science observation of plastics in coastal ecosystems by high-school students - Catarino, Ana I.; Mahu, Edem; Severin, Marine I.; Akpetou, Lazare Kouame; Annasawmy, Pavanee; Asuquo, Francis Emile; Beckman, Fiona; Benomar, Mostapha; Jaya-Ram, Annette; Malouli, Mohammed; Mees, Jan; Monteiro, Ivanice; et al. (Frontiers in Marine Science, 2023)
The Citizen Observation of Local Litter in coastal ECosysTems (COLLECT) project (2021-2022) is a citizen science initiative, supported by the Partnership for Observation of the Global Ocean (POGO), which aimed to acquire distribution and abundance data of coastal plastic litter in seven countries: in Africa (Benin, Cabo Verde, Côte d’Ivoire, Ghana, Morocco, Nigeria) and Asia (Malaysia). In this paper, we describe the workflow used to establish and run this project, as well as the methodologies to acquire data. The COLLECT project consisted of training local students (15 - 18 years old) from ten second cycle institutions (“high schools”) on sampling and analyzing macro-, meso- and microplastics in beach sediments, using a quantitative assessment protocol. We further describe in detail the methodologies applied in assessing the impact of participating in the activities from a social sciences perspective. All documents and materials resulting from this project will be open access and available according to the FAIR Principles (Findable, Accessible, Interoperable, and Reusable). The results and outcomes from COLLECT will contribute to expanding knowledge and establishing baseline information on coastal plastic pollution, with citizen science being an enabler of open science, allowing data to be freely available to the public, academics and policymakers. Expected results from the use of the COLLECT protocol globally will further contribute to the identification of hotspots of coastal plastic litter, and bring awareness to local communities on the potential consequences of plastic pollution. The COLLECT project actively contributes with data suitable to survey plastic litter to the United Nations’ Sustainable Development Goals (UN SDGs), in particular to SDG 14, on the sustainable use of the ocean.